Can Asperger syndrome be distinguished from autism? An anatomic likelihood meta-analysis of MRI studies - Yu, Kevin K. (Canadian Medical Association, 2011)
BACKGROUND: The question of whether Asperger syndrome can be distinguished from autism has attracted much debate and may even incur delay in diagnosis and intervention. Accordingly, there has been a proposal for Asperger syndrome to be subsumed under autism in the forthcoming Diagnostic and Statistical Manual of Mental Disorders, fifth edition, in 2013. One approach to resolve this question has been to adopt the criterion of absence of clinically significant language or cognitive delay — essentially, the “absence of language delay.” To our knowledge, this is the first meta-analysis of magnetic resonance imaging (MRI) studies of people with autism to compare absence with presence of language delay. It capitalizes on the voxel-based morphometry (VBM) approach to systematically explore the whole brain for anatomic correlates of delay and no delay in language acquisition in people with autism spectrum disorders. METHODS: We conducted a systematic search for VBM MRI studies of grey matter volume in people with autism. Studies with a majority (at least 70%) of participants with autism diagnoses and a history of language delay were assigned to the autism group (n = 151, control n = 190). Those with a majority (at least 70%) of individuals with autism diagnoses and no language delay were assigned to the Asperger syndrome group (n = 149, control n = 214). We entered study coordinates into anatomic likelihood estimation meta-analysis software with sampling size weighting to compare grey matter summary maps driven by Asperger syndrome or autism. RESULTS: The summary autism grey matter map showed lower volumes in the cerebellum, right uncus, dorsal hippocampus and middle temporal gyrus compared with controls; grey matter volumes were greater in the bilateral caudate, prefrontal lobe and ventral temporal lobe. The summary Asperger syndrome map indicated lower grey matter volumes in the bilateral amygdala/hippocampal gyrus and prefrontal lobe, left occipital gyrus, right cerebellum, putamen and precuneus compared with controls; grey matter volumes were greater in more limited regions, including the bilateral inferior parietal lobule and the left fusiform gyrus. Both Asperger syndrome and autism studies reported volume increase in clusters in the ventral temporal lobe of the left hemisphere. LIMITATIONS: We assigned studies to autism and Asperger syndrome groups for separate analyses of the data and did not carry out a direct statistical group comparison. In addition, studies available for analysis did not capture the entire spectrum, therefore we cannot be certain that our findings apply to a wider population than that sampled. CONCLUSION: Whereas grey matter differences in people with Asperger syndrome compared with controls are sparser than those reported in studies of people with autism, the distribution and direction of differences in each category are distinctive.